Factors Affecting the Effectiveness of School Staff Meetings: A Study of Two High Schools in Northern Kenya - Bonyo, Benard Odhiambo (African Journal of Education,Science and Technology (AJEST), 2017)
Professionalism requires self determination, participation and the ability to make important decisions about the nature of one’s work. However, in schools, often times, teachers outside their classrooms have little say about school policies, procedures, curriculum development, and other matters that have a direct bearing on the quality and effectiveness of their work. School staff meetings where their ideas would be heard may be occasionally unprofessionally held, with members unprepared and the leaders doing most of the talking. This study investigated the factors affecting the effectiveness of school staff meetings in two high schools in Northern Kenya. Using qualitative case study design, the study sought to establish whether there were policies guiding the conduct of staff meetings, the practice of staff meetings and how policy and practice affect the effectiveness of staff meetings. Two teachers per school were randomly sampled for interviews, two heads of departments per school, the deputy principal and the principal of each school were also interviewed, 4 staff meetings were observed and meeting documents such as minutes and notification of meetings analyzed in the two schools. The findings indicate that inadequate policies or lack of them, inadequate knowledge of meeting protocol, haphazard formulation of agenda, lack of teacher involvement in meeting preparations and communication hamper the best practice of staff meetings hence ineffectiveness. An improved and structured bottom up model for school staff meetings is recommended if schools are to manage staff meetings professionally and conventionally. It is also suggested that for effective school staff meetings to be achieved, an action research study should be carried out in institutions with a view to improving the conduct of staff meetings in schools.